2012
DOI: 10.1111/j.1751-7893.2012.00341.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical differences between early‐ and late‐onset social anxiety disorders

Abstract: Symptom severity and behavioural inhibitions, especially in social/school situations, were clinical characteristics that differentiated between early- and late-onset SAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
(72 reference statements)
0
3
0
1
Order By: Relevance
“…Within this framework, our results seem in line with previous studies that reported how patients with an early onset SAD frequently show higher levels of behavioral inhibition and impairment, as well as a higher frequency of comorbidities, including with OCD. 42,43 Taken together, this pattern might also suggest a possible role of OCD traits in worsening and chronicizing SAD symptoms. 24,[42][43][44][45][46] These findings seem to be in agreement with those of a previous study, 46 which evaluated the relationship between SAD and "hikikomori syndrome," a severe form of social withdrawal defined as isolation lasting more than 6 months.…”
Section: Cns Spectrumsmentioning
confidence: 78%
See 1 more Smart Citation
“…Within this framework, our results seem in line with previous studies that reported how patients with an early onset SAD frequently show higher levels of behavioral inhibition and impairment, as well as a higher frequency of comorbidities, including with OCD. 42,43 Taken together, this pattern might also suggest a possible role of OCD traits in worsening and chronicizing SAD symptoms. 24,[42][43][44][45][46] These findings seem to be in agreement with those of a previous study, 46 which evaluated the relationship between SAD and "hikikomori syndrome," a severe form of social withdrawal defined as isolation lasting more than 6 months.…”
Section: Cns Spectrumsmentioning
confidence: 78%
“…42,43 Taken together, this pattern might also suggest a possible role of OCD traits in worsening and chronicizing SAD symptoms. 24,[42][43][44][45][46] These findings seem to be in agreement with those of a previous study, 46 which evaluated the relationship between SAD and "hikikomori syndrome," a severe form of social withdrawal defined as isolation lasting more than 6 months. 47 This study showed that SAD patients fulfilling the criteria for hikikomori had an earlier onset and more severe symptoms than non-hikikomori SAD, together with higher rates of a comorbid OCD.…”
Section: Cns Spectrumsmentioning
confidence: 78%
“…13 Several studies have compared the outcomes of early versus late onset of anxiety disorders. Early (childhood) onset has been associated with more severe psychopathology and comorbidity, [14][15][16] more avoidance behaviour, 17 and even higher rates of suicide. 18 Although outcomes of early anxiety disorder onset demonstrate the need for accurate information about the AOO, there is wide variation in the reported mean AOO between studies and for anxiety disorder subtypes.…”
Section: Limitationsmentioning
confidence: 99%
“…Genellenmiş sosyal anksiyete bozukluğunun ayrıca, niceliksel olarak yapılan incelemelerle ortaya koyulmuş olduğu gibi sadece daha fazla sosyal ortamda yaşanılan sosyal anksiyete ile değil, düşük öz saygı, çocukluk döneminde aşırı utangaçlık, sosyal beceri eksikliği, nörotizm (Hoffman ve Roth 1992), daha fazla davranışsal baskılanma (Lim 2013) ile ilişkili olduğunu belirten araştırmalar da bulunmaktadır. Sosyal anksiyete bozukluğunun alt tiplerini çevresel uyaranlara aşırı duyarlılık ve zarardan kaçınma davranışları açısından karşılaştıran bir araştırmada ise genellenmiş sosyal anksiyete bozukluğu belirtileri gösteren bireylerin genellenmemiş sosyal anksiyete bozukluğu belirtileri gösteren bireylere kıyasla çevresel tehditlere daha fazla duyarlı oldukları, olası bir zarardan kaçınmak amacıyla yenilik arayışında bulunmadıkları ve davranışsal inhibisyona yöneldikleri görülmüştür (Hofmann ve Bitran 2007).…”
Section: Demografik Ve Davranışsal öZelliklere İlişkin Farklılıklarunclassified